2021
DOI: 10.48550/arxiv.2112.11107
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The QCD chiral phase transition for different numbers of quark flavours

Abstract: We present results from a comprehensive study of the location of the chiral critical surface, which separates regions of first-order chiral transitions from analytic crossovers, in the bare parameter space of lattice QCD with unimproved staggered fermions. We study the theories with 𝑁 f ∈ [2, 8] and trace the chiral critical surface along diminishing lattice spacing, with 𝑁 𝜏 = {4, 6, 8}. This allows for an extrapolation to the lattice chiral limit, where the surface has to terminate in a tricritical line, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 17 publications
0
0
0
Order By: Relevance
“…When increasing m s , the first order phase transition and the line of tricritical points might persist until m s = ∞, as depicted in Figure 4.4, or the first order phase transition might end in a line of O(4) points as depicted in Figure 4.5. In [91] it is even suggested that the O(4) line extends down to 0, so that there is no first order chiral region at all and the left axis consists entirely of O(4) points.…”
Section: The Columbia Plotmentioning
confidence: 99%
See 1 more Smart Citation
“…When increasing m s , the first order phase transition and the line of tricritical points might persist until m s = ∞, as depicted in Figure 4.4, or the first order phase transition might end in a line of O(4) points as depicted in Figure 4.5. In [91] it is even suggested that the O(4) line extends down to 0, so that there is no first order chiral region at all and the left axis consists entirely of O(4) points.…”
Section: The Columbia Plotmentioning
confidence: 99%
“…From these results it is possible to extrapolate to Β΅ = 0 and learn about the usual Columbia plot this way. It is also possible to simulate at non-integer N f [91], then extend these results into the chiral limit where the surface has to end in a tricritical line and analyse it via tricritical scaling relations. Another difficulty regarding the Columbia plot are discretisation effects: the Z 2 lines shift with decreasing lattice spacing [95], which is depicted in Figure 4.6.…”
Section: Crossovermentioning
confidence: 99%